Effect analysis of stress-intensity-factor-range decreasing rate for obtaining threshold stress-intensity-factor-range. (December 2019) - Li, Bochuan; Koyama, Motomichi; Hamada, Shigeru; Noguchi, Hiroshi
Highlights: Δ K th is dependent on the Δ K decreasing rate. This study performed PICC analysis with the Dugdale model. The dependence of material properties on Δ K th of long crack was studied. The rate value proposed by ASTM is valid for all materials within 10% error. Abstract: The threshold stress intensity factor range Δ K th can be obtained using the Δ K decreasing method. Because Δ K th is dependent on the Δ K decreasing rate, the rate is regulated by the American Society of Testing Materials standard. However, the rate was derived under specific conditions, and its applicability to materials with physical properties different from ordinary steel has not been clarified. To address this issue, this study performed plasticity-induced-crack-closure analysis with the Dugdale model. The dependence of material properties on Δ K th of long crack was determined for steel, aluminum and magnesium. The results showed that the rate value proposed by the standard is valid for all materials with different yield strengths and different Young's moduli within 10% error.